Design and analysis plant factory with artificial light - Boonmee, Chaiyant; Wongsuriya, Wipada; Homjan, Jeerawan; Kiatsookkanatorn, Paiboon; Sritanauthaikorn, Patcharanan; Wannakam, Khanittha; Watjanatepin, Napat (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
It has been challenging to construct an autonomously controlled plant factory with artificial light (PFAL). It is also useful in engineering and bioscience research and education. The purpose of this research is to design and construct a micro-scale PFAL (µPFAL) with automatic environment control for a university project. Then, analyze the effectiveness of managing temperature, humidity, pH, EC, and CO2 on crop production, as well as the cost, and benefit of µPFAL. The µPFAL is made up of LED lighting, air condition, vertical cultivation, EC-pH regulation, a CO2 supply unit, and environmental control and monitoring. Control was provided via Arduino with PC monitor. For economic evaluation, cost-benefit analysis was used. The results of the control environment in µPFAL were achieved with a deviation of less than 2.5%. An Arduino-based environmental control system with a computer for monitoring was suited for university’s PFAL.Our µPFAL could produce 80.45 g/head fresh weight of green oak lettuce, the lettuce’s yield of 19 kg/m2/y. The payback period of µPFAL is 3.28 years, net present value of 82,543.30 THB, an internal rate of return of 24% and the B/C ratio of 1.22. Future research should include solar energy to assist µPFAL in meeting its sustainable goal.